Discovery of Recent thecideide brachiopods (Order: Thecideida, Family: Thecideidae) in Sulawesi, Indonesian Archipelago, with implications for reproduction and shell size in the genus Ospreyella - Simon, Eric; Hoffmann, Jana (Zootaxa, 2013)
For the first time thecideide brachiopods have been discovered in the Indonesian Archipelago. All specimens were collected in a water depth of 30 m from an old shipwreck, the “Mutiara”, which represents a remarkable habitat for these cryptic brachiopods despite its artificial nature. The thecidellinine species Minutella cf. minuta and the lacazelline species Ospreyella mutiara n. sp. are described and illustrated comprehensively, including their shell ontogeny. The inclusion of the new species O. mutiara in the genus Ospreyella Lüter and Wörheide, 2003 is based on results of an integrated approach combining morphological, ontogenetic and genetic studies. Relevant morphological characters diagnostic for Ospreyella are established. In addition, all Recent lacazelline brachiopod genera are confirmed as valid taxa using molecular methods. The small body size of O. mutiara and the weakly developed brachidium in comparison to other Ospreyella species as a consequence of heterochrony is discussed in more detail. O. mutiara is the first species of the exclusively gonochoristic genus Ospreyella for which hermaphroditism is now documented.